A composite thin film semiconductor photocatalyst and preparation method thereof
Through the electrospinning technology of ZnO, TiO2 and WO3 composite metal oxides and sodium borohydride reduction method, the problem of wide band gap of metal oxide photocatalysts is solved, and the high absorbance and mechanical properties are improved, which is suitable for photoelectric catalytic reactions .
Patent Information
- Application Number
- CN202310252041.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-16
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-03-16
AI Technical Summary
The band gap width of existing metal oxide photocatalysts leads to low solar energy utilization and catalytic activity, and commonly used improvement methods have a destructive effect on the mechanical properties of fiber films.
The nanofiber membrane was prepared by electrospinning using composite metal oxides of ZnO, TiO2 and WO3, and reduced with sodium borohydride solution to shorten the band gap width and enhance the optical absorption capacity.
The absorbance and mechanical properties of the composite film are significantly improved, the integrity of the fiber film is maintained, and the absorbance is increased to 1.5 times that of the prior art, and is suitable for photoelectric catalytic reactions.
Smart Images

Figure CN116328756B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a semiconductor photocatalyst, in particular to a composite thin film semiconductor photocatalyst, and also to a method for preparing the photocatalyst. Background Art
[0002] Semiconductor materials are one of the important cornerstones of the development of photocatalysts. The photocatalytic activity of metal oxides mainly depends on their absorption of visible and infrared light and their ability to separate photogenerated carriers. 2 , ZnO and WO 3 Based on semiconductor catalysts are the most widely used photocatalysts, however, the photogenerated electron-hole pairs of metal oxides are very easy to recombine, resulting in low solar energy utilization and catalytic activity. 2 The band gap of ZnO is 3.2 eV, and it shows obvious optical response in the ultraviolet range. The band structure of ZnO is similar to that of TiO 2 Basically the same, WO 3 The band gap is between 2.4 and 2.8 eV. The wider the band gap, the narrower the range of visible light absorption and the lower the efficiency of visible light utilization.
[0003] In the prior art, the methods for narrowing the band gap of metal oxide photocatalysts usually include element doping, using co-catalysts, constructing heterojunctions, etc. to improve the catalytic performance of semiconductor metal oxide photocatalysts so that they can absorb visible light for catalytic reactions. However, these methods are often applied to the preparation of layered, powdered or granular nano-photocatalysts, and these methods usually destroy the mechanical properties of the fiber film itself. For example, the application of hydrothermal method for element doping destroys the integrity of the fiber film; calcination through atmosphere affects the flexibility of the fiber film. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide a composite thin film semiconductor photocatalyst with good mechanical properties, narrow band gap and strong visible light absorbance. The second purpose is to provide a method for preparing the above-mentioned photocatalyst.
[0005] Technical solution: The composite thin film semiconductor photocatalyst of the present invention is ZnO, TiO 2 and WO 3 The composite metal oxides, calculated by the mass of Zn, Ti and W, are ZnO, TiO 2 and WO 3 The mass ratio is 1~10:5~20:1~8.
[0006] Preferably, the synthetic metal oxides ZnO, TiO 2 and WO 3 The mass ratio of the precursors is 1:10~15:0.5~7.5.
[0007] The method for preparing the above-mentioned photocatalyst comprises the following steps:
[0008] (1) Mix ethanol, polyvinyl pyrrolidone, ZIF-8, and ammonium tungstate, and then add acetic acid and tetraisopropyl titanate to obtain a precursor solution;
[0009] (2) preparing a precursor nanofiber membrane by electrospinning and calcining;
[0010] (3) The fiber membrane obtained after calcination is reduced with sodium borohydride solution to obtain ZnO / TiO 2 / WO 3 Composite thin film semiconductor photocatalysts.
[0011] Preferably, in step (1), in the precursor solution, the mass ratio of polyvinyl pyrrolidone, ethanol, ZIF-8, ammonium tungstate, acetic acid, and tetraisopropyl titanate is 3-6:20-40:1:0.7-7.5:10-15:20-50.
[0012] Preferably, in step (2), the spinning conditions are: voltage: 20-25 kV, flow rate: 0.4-0.5 ml / h; the calcination temperature is 600° C., insulation time is 2-5 h, and heating rate is 2-5° C. / min.
[0013] Preferably, in step (3), the mass fraction of the sodium borohydride solution is 10 to 30 wt %, and 2 to 8 ml of the sodium borohydride solution is added per milligram of fiber membrane.
[0014] Principle of the invention: The present invention prepares a precursor spinning solution by compounding ZIF-8, ammonium tungstate and tetraisopropyl titanate, and calcines after spinning to obtain a membrane with a thickness of 6 to 8 microns and extremely strong mechanical properties. During the calcination process, the fiber grains grow excessively and the grain boundaries are easily broken. The compounding of ZIF-8, ammonium tungstate and tetraisopropyl titanate can inhibit the excessive growth between the grains and reduce the grain size, thereby obtaining a composite fiber membrane with strong mechanical properties. The prepared fiber membrane is immersed in a sodium borohydride solution for reduction. Sodium borohydride has extremely strong reducing properties and can prepare oxygen vacancies at room temperature. For example, oxygen vacancies can also be prepared by reduction with hydrazine hydrate, but hydrazine hydrate needs to react in an alkaline environment, and its reducing property is weaker than that of sodium borohydride. Through the reduction of sodium borohydride, oxygen vacancy defects are introduced into the composite semiconductor photocatalyst, the original lattice structure is changed, the band gap width of the composite semiconductor material is shortened, and it has visible light response ability; gray ZnO / TiO 2 / WO 3 The composite thin film semiconductor photocatalyst introduces oxygen vacancies through reduction with sodium borohydride solution to reduce the band gap, thereby achieving the effect of expanding optical absorption and improving photocatalytic performance.
[0015] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The absorbance is greatly increased, with the ultraviolet light absorbance reaching a maximum of 7.163, the visible light absorbance reaching a maximum of 5.934, and the infrared light absorbance reaching a maximum of 4.099, which is 1.5 times that of the prior art; (2) The strength of the composite film is increased, which can maintain the integrity of the fiber membrane in the photoelectrocatalytic methane flow cell experiment. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a physical picture of the nanofiber membrane before sodium borohydride reduction;
[0017] Figure 2 ZnO / TiO after sodium borohydride reduction 2 / WO 3 Physical picture of fiber membrane;
[0018] Figure 3 This is a physical picture of the flexibility of the nanofiber membrane before sodium borohydride reduction. DETAILED DESCRIPTION
[0019] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0020] Example 1
[0021] ZnO / TiO 2 / WO 3 The preparation method of the composite thin film semiconductor photocatalyst material is specifically as follows:
[0022] (1) Add 0.6 g PVP and 4.5 ml ethanol to the culture bottle and stir for 1.5 h. After they are completely dissolved, add 0.128 g ZIF-8 and 0.08 g ammonium tungstate and stir overnight. Add 3 ml acetic acid and stir for 15 min. Then add 2.5 ml tetraisopropyl titanate and stir for 15 min to obtain a precursor solution.
[0023] (2) Preparing a precursor nanofiber membrane by an electrospinning method, the spinning parameters are voltage: 20-25 kV, spinning speed: 0.4-0.5 ml / h; calcining, the calcination conditions are 600 ° C, keeping warm for 2 hours, and the heating rate is 3 ° C / min;
[0024] (3) The calcined fiber membrane was reduced with a 20 wt% sodium borohydride solution to obtain a ZnO / TiO2 film with a thickness of 6 μm. 2 / WO 3 Composite thin film semiconductor photocatalysts.
[0025] Example 2
[0026] ZnO / TiO2 / WO 3 The preparation method of the composite thin film semiconductor photocatalyst material is as follows: compared with Example 1, the mass percentage of the sodium borohydride solution is changed:
[0027] (1) Add 0.6 g PVP and 4.5 ml ethanol to the culture bottle and stir for 1.5 h. After they are completely dissolved, add 0.128 g ZIF-8 and 0.08 g ammonium tungstate and stir overnight. Add 3 ml acetic acid and stir for 15 min. Then add 2.5 ml tetraisopropyl titanate and stir for 15 min to obtain a precursor solution.
[0028] (2) Preparing a precursor nanofiber membrane by an electrospinning method, the spinning parameters are voltage: 20-25 kV, spinning speed: 0.4-0.5 ml / h; calcining, the calcination conditions are 600 ° C, keeping warm for 2 hours, and the heating rate is 3 ° C / min;
[0029] (3) The calcined fiber membrane was reduced with a 10 wt% sodium borohydride solution to obtain a ZnO / TiO2 film with a thickness of 6 μm. 2 / WO 3 Composite thin film semiconductor photocatalysts.
[0030] Example 3
[0031] ZnO / TiO 2 / WO 3 The preparation method of the composite thin film semiconductor photocatalyst material is as follows: compared with Example 1, the mass percentage of the sodium borohydride solution is changed:
[0032] (1) Add 0.6 g PVP and 4.5 ml ethanol to the culture bottle and stir for 1.5 h. After they are completely dissolved, add 0.128 g ZIF-8 and 0.08 g ammonium tungstate and stir overnight. Add 3 ml acetic acid and stir for 15 min. Then add 2.5 ml tetraisopropyl titanate and stir for 15 min to obtain a precursor solution.
[0033] (2) Preparing a precursor nanofiber membrane by an electrospinning method, the spinning parameters are voltage: 20-25 kV, spinning speed: 0.4-0.5 ml / h; calcining, the calcination conditions are 600 ° C, keeping warm for 2 hours, and the heating rate is 3 ° C / min;
[0034] (3) The calcined fiber membrane was reduced with a 30 wt% sodium borohydride solution to obtain a ZnO / TiO2 film with a thickness of 6 μm. 2 / WO 3 Composite thin film semiconductor photocatalysts.
[0035] Comparative Example 1
[0036] ZnO / TiO 2 / WO 3 The method for preparing the fiber membrane, compared with Example 1, eliminates the step of reducing the fiber membrane obtained after calcination with a sodium borohydride solution:
[0037] (1) Add 0.6 g PVP and 4.5 ml ethanol to the culture bottle and stir for 1.5 h. After they are completely dissolved, add 0.128 g ZIF-8 and 0.08 g ammonium tungstate and stir overnight. Add 3 ml acetic acid and stir for 15 min. Then add 2.5 ml tetraisopropyl titanate and stir for 15 min to obtain a precursor solution.
[0038] (2) The precursor nanofiber membrane was prepared by electrospinning, the spinning parameters were voltage: 20-25 kV, spinning speed: 0.4-0.5 ml / h; calcination was performed, the calcination conditions were 600 °C, heat preservation for 2 h, and the heating rate was 3 °C / min to obtain ZnO / TiO 2 / WO 3 Fiber membrane.
[0039] Comparative Example 2
[0040] ZnO / TiO 2 / WO 3 The preparation method of the composite thin film semiconductor photocatalyst material is as follows: compared with Example 1, the mass percentage of the sodium borohydride solution is changed:
[0041] (1) Add 0.6 g PVP and 4.5 ml ethanol to the culture bottle and stir for 1.5 h. After they are completely dissolved, add 0.128 g ZIF-8 and 0.08 g ammonium tungstate and stir overnight. Add 3 ml acetic acid and stir for 15 min. Then add 2.5 ml tetraisopropyl titanate and stir for 15 min to obtain a precursor solution.
[0042] (2) Preparing a precursor nanofiber membrane by an electrospinning method, the spinning parameters are voltage: 20-25 kV, spinning speed: 0.4-0.5 ml / h; calcining, the calcination conditions are 600 ° C, keeping warm for 2 hours, and the heating rate is 3 ° C / min;
[0043] (3) The fiber membrane obtained after calcination was reduced with a 5 wt% sodium borohydride solution to obtain ZnO / TiO 2 / WO 3 Composite thin film semiconductor photocatalyst; the prepared composite film changes from gray to white within 5 minutes.
[0044] Comparative Example 3
[0045] ZnO / TiO 2 / WO 3The preparation method of the composite thin film semiconductor photocatalyst material is as follows: compared with Example 1, the mass percentage of the sodium borohydride solution is changed:
[0046] (1) Add 0.6 g PVP and 4.5 ml ethanol to the culture bottle and stir for 1.5 h. After they are completely dissolved, add 0.128 g ZIF-8 and 0.08 g ammonium tungstate and stir overnight. Add 3 ml acetic acid and stir for 15 min. Then add 2.5 ml tetraisopropyl titanate and stir for 15 min to obtain a precursor solution.
[0047] (2) Preparing a precursor nanofiber membrane by an electrospinning method, the spinning parameters are voltage: 20-25 kV, spinning speed: 0.4-0.5 ml / h; calcining, the calcination conditions are 600 ° C, keeping warm for 2 hours, and the heating rate is 3 ° C / min;
[0048] (3) The fiber membrane obtained after calcination was reduced using a 40 wt % sodium borohydride solution. During the washing and reduction process, the composite film was broken and could not maintain its shape.
[0049] Comparative Example 4
[0050] ZnO / TiO 2 The preparation method of the composite thin film semiconductor photocatalyst material, compared with Example 1, removes ammonium tungstate, specifically:
[0051] (1) Add 0.6 g PVP and 4.5 ml ethanol to the culture bottle and stir for 1.5 h. After they are completely dissolved, add 0.128 g ZIF-8 and stir overnight. Add 3 ml acetic acid and stir for 15 min. Then add 2.5 ml tetraisopropyl titanate and stir for 15 min to obtain a precursor solution.
[0052] (2) The precursor nanofiber membrane was prepared by an electrospinning method, with the spinning parameters being voltage: 20-25 kV, spinning speed: 0.4-0.5 ml / h; calcination was performed, with the calcination conditions being 600 °C, keeping warm for 2 h, and a heating rate of 3 °C / min. After calcination, the film was damaged and lacked self-support.
[0053] Comparative Example 5
[0054] ZnO / WO 3 The preparation method of the composite thin film semiconductor photocatalyst material, compared with Example 1, removes tetraisopropyl titanate, specifically:
[0055] (1) Add 0.6 g PVP and 4.5 ml ethanol to the culture bottle and stir for 1.5 h. After they are completely dissolved, add 0.128 g ZIF-8 and 0.08 g ammonium tungstate and stir overnight. Add 3 ml acetic acid and stir for 15 min to obtain a precursor solution.
[0056] (2) The precursor nanofiber membrane was prepared by an electrospinning method, with the spinning parameters being voltage: 20-25 kV, spinning speed: 0.4-0.5 ml / h; calcination was performed, with the calcination conditions being 600°C, keeping warm for 2 hours, and a heating rate of 3°C / min; after calcination, the film was damaged and lacked self-support.
[0057] Comparative Example 6
[0058] TiO 2 / WO 3 The preparation method of the composite thin film semiconductor photocatalyst material, compared with Example 1, removes ZIF-8, specifically:
[0059] (1) Add 0.6 g PVP and 4.5 ml ethanol to the culture bottle and stir for 1.5 h. After it is completely dissolved, add 0.08 g ammonium tungstate and stir overnight. Add 3 ml acetic acid and stir for 15 min to obtain a precursor solution.
[0060] (2) The precursor nanofiber membrane was prepared by an electrospinning method, with the spinning parameters being voltage: 20-25 kV, spinning speed: 0.4-0.5 ml / h; calcination was performed, with the calcination conditions being 600°C, keeping warm for 2 hours, and a heating rate of 3°C / min; after calcination, the film was damaged and lacked self-support.
[0061] The composite films of the embodiment and the comparative example were subjected to ultraviolet infrared spectrum absorption test, and the results are shown in the following table:
[0062] Table 1. UV-IR spectrum absorption test results
[0063] Ultraviolet light Visible light Infrared light Absorbance of Example 1 7.163~5.934 5.934~4.099 4.099~3.984 Absorbance of Example 2 6.284~5.228 5.228~3.563 3.563~3.457 Absorbance of Example 3 7.104~5.803 5.803~3.978 3.978~3.862 Absorbance of Comparative Example 1 4.298~3.742 3.742~2.686 2.686~2.584 Absorbance of Comparative Example 2 6.752~5.648 5.648~3.896 3.896~3.732
[0064] As shown in the table above, the ZnO / TiO 2 / WO 3 Composite thin film semiconductor photocatalyst, the absorbance is much higher than that of ZnO / TiO without sodium borohydride treatment 2 / WO 3The fiber membrane has an absorbance of about 1.5 times that of the fiber membrane without sodium borohydride treatment. The fiber membrane treated with sodium borohydride is gray in appearance. At the same time, due to the reduction of sodium borohydride to generate oxygen vacancies, the band gap width of the composite semiconductor catalyst is reduced, and the absorbance of the fiber membrane is enhanced; among them, the absorbance of Example 1 is the best, and the appropriate oxygen vacancy concentration can improve the photocatalytic performance. The oxygen vacancies can capture photogenerated electrons and delay the recombination of photogenerated electron-hole pairs. At the same time, the oxygen vacancies have a positive effect on the adsorption of surface oxygen-containing groups, improve the photocatalytic reaction ability, and maintain the complete morphology of the fiber membrane; in addition, in Comparative Example 2, which uses 5wt% sodium borohydride solution for reduction, because the content of sodium borohydride solution is too little, the composite film is very easy to be oxidized and the color returns to white, and the absorbance is reduced; in Comparative Example 3, which uses 40wt% sodium borohydride solution for reduction, the content of sodium borohydride solution is too much, and the bubbles of sodium borohydride will affect the occurrence of the reduction reaction and destroy the morphology of the membrane during the washing process. At the same time, the combination of the three components can inhibit the excessive growth between the grains. In comparative examples 4-6, the oxides are combined in pairs, which cannot achieve the effect of inhibiting the excessive growth between the grains. Therefore, their mechanical properties are poor, they lack self-support, and they are damaged after the calcination step.
Claims
1. A composite thin film semiconductor photocatalyst, characterized in that: The photocatalyst is a composite metal oxide of ZnO, TiO2 and WO3, and the mass ratio of ZnO, TiO2 and WO3 is 1-10:5-20:1-8 based on the mass of Zn, Ti and W. The photocatalyst is prepared according to the following steps: (1) Mix ethanol, polyvinyl pyrrolidone, ZIF-8, and ammonium tungstate, and then add acetic acid and tetraisopropyl titanate to obtain a precursor solution, wherein the mass ratio of polyvinyl pyrrolidone, ethanol, ZIF-8, ammonium tungstate, acetic acid, and tetraisopropyl titanate is 3-6:20-40:1:0.7-7.5:10-15:20-50; (2) preparing a precursor nanofiber membrane by an electrospinning method, and calcining the nanofiber membrane; (3) The nanofiber membrane is reduced with a sodium borohydride solution, wherein the amount of the sodium borohydride solution added is: 2 to 8 mL of the sodium borohydride solution per mg of the nanofiber membrane, thereby obtaining a ZnO / TiO2 / WO3 composite thin film semiconductor photocatalyst.
2. The photocatalyst according to claim 1, characterized in that The mass ratio of the precursors of the synthetic metal oxide ZnO, TiO2 and WO3 is 1:10-15:0.5-7.
5.
3. The photocatalyst according to claim 1, characterized in that In step (2), the spinning conditions are: voltage: 20-25KV, flow rate: 0.4-0.5mL / h.
4. The photocatalyst according to claim 1, characterized in that In step (2), the calcination temperature is 600° C., the temperature is kept for 2 to 5 hours, and the heating rate is 2 to 5° C. / min.
5. The photocatalyst according to claim 1, characterized in that The mass fraction of the sodium borohydride solution is 10-30 wt %.
